2016
DOI: 10.9734/or/2016/29870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phaco Energy and Complications for Conventional Phacoemulsification and 25-gauge Phacovitrectomy Surgery

Abstract: Aim:To compare cumulative dissipated energy (CED), intraoperative and postoperative complications in eyes underwent conventional phacoemulsification and 25-Gauge phacovitrectomy surgery. Study Design: Retrospective, comparative case series in ophthalmology clinic of Ulucanlar Eye Education and Research Hospital. Methodology: A total of 140 eyes underwent conventional phacoemulsification and 25-Gauge phacovitrectomy surgeries were evaluated. CDE intraoperative, early and late postoperative surgical outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Ultrasonic energy delivered into the eye during phacoemulsification surgery is presented as CDE in the Centurion system. CDE represents the efficacy of the phacoemulsification procedure, and the delivery of minimum ultrasonic energy is desirable [ 9 ]. According to the results of this study, required CDE is higher in eyes with corneal opacity when compared with eyes with clear cornea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic energy delivered into the eye during phacoemulsification surgery is presented as CDE in the Centurion system. CDE represents the efficacy of the phacoemulsification procedure, and the delivery of minimum ultrasonic energy is desirable [ 9 ]. According to the results of this study, required CDE is higher in eyes with corneal opacity when compared with eyes with clear cornea.…”
Section: Discussionmentioning
confidence: 99%
“…On torsional mode, frequency of movements in phaco tip is 32 kHz and this is 80% of the frequency of movements delivered with conventional mode. In addition, torsional mode provides nucleus emulsification with rotary oscillations, while conventional mode provides only forward and backward oscillations of the phaco tip [ 9 ]. Fakhry et al [ 14 ] reported torsional mode, which provides lower ultrasound energy and more effective phacoemulsification when compared with the conventional mode.…”
Section: Discussionmentioning
confidence: 99%